(untitled) (Conferencea, 2022)
President Of The Republic Of Uzbekistan Sh.In Mirziyoyev’s appeal to the Supreme Assembly on January 24, 2020, it was proposed to name 2020 "year of development of science, enlightenment and digital economy", to increase the level of coverage of school graduates with higher education, to revise the system of Educational Directions and disciplines taught, to reduce subjects unrelated to the specialty, to transfer the educational process, he emphasized that the issues of wide implementation of public-private mechanisms in the field of education are one of the current issues.